Lefschetz numbers and asymptotic periods - Gryszka, Karol (Analitic and Algebraic Geometry 4, 2022)
In this note we prove several results linking Lefschetz numbers with asymptotic behaviour of the orbit in flows. With the aid of the Lefschetz fixed point theorem and the presence of a non-trivial limit set we prove the existence of asymptotically non-periodic orbits.